Latihan Asertif terhadap Depresi Caregiver Pasien Penyakit Jantung - Fitri Wijayati (LPPM STIKes Karya Kesehatan, 2017)
Depression often found in caregiver of patient with heart disease. The purpose of this reesearch was to investigate the influence of assertiveness training on depressed condition of patient heart disease’s caregivers. This is a pre-post with nonequivalent control group study, and there were 70 subjects participated with consecutive technique (35 in experimental groups; 35 in comparison group). Data collected before and after therapy by using Zung Self-rating Depression Scale. Anova and Samples t-test were used to analyze the data. There is a significant decrease on depression scores after assertiveness training (p value < 0,05). Caregivers would have benefit of mental health improvement, and this psychotherapy could be provided as a reference to overcome depression of caregiver who taking care of patient with heart disease.